Beautifying housing made of composite material and preparation method of beautifying housing

By adopting chemical modification and melt blending processes of nanotitanium dioxide, isocyanate-terminated polypropylene carbonate and 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol in the beautified shell, the problem of insufficient impact resistance, UV resistance and aging resistance of beautified shell is solved, and higher performance and longer service life are achieved.

CN119752087AInactive Publication Date: 2025-04-04GUANGZHOU CHANGTONG ELECTROMECHANICAL EQUIP INSTALLATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510058852.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing beautification shells are insufficient in terms of impact resistance, UV resistance and aging resistance, especially when used outdoors for a long time, they are prone to damage, aging and reducing mechanical properties.

Method used

Nanotitanium dioxide, isocyanate-capped polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol and other materials were prepared through chemical modification and melt blending processes to prepare composite materials with excellent impact resistance, UV resistance and aging resistance.

Benefits of technology

It significantly improves the impact resistance, UV resistance and aging resistance of the beautified shell, extends the service life, reduces maintenance costs, and maintains stable operation in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752087A_ABST
    Figure CN119752087A_ABST
Patent Text Reader

Abstract

The invention discloses a beautifying housing made of a composite material and a preparation method, and belongs to the technical field of high polymer materials. The beautifying housing is used for solving the technical problem that the impact resistance, the ultraviolet resistance and the aging resistance of the beautifying housing need to be further improved in the prior art. The preparation method of the beautifying housing made of the composite material comprises the following steps: carrying out a reaction on aminated titanium dioxide grafted poly (propylene carbonate) and 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl) phenol to obtain modified poly (propylene carbonate); mixing the modified polypropylene carbonate, polypropylene and an initiator in inert gas, and heating to react to obtain an intermediate I after the reaction is finished; carrying out melt blending on the intermediate I, glass fiber, silicone rubber, an antioxidant, a UV absorbent and a lubricant, and after melt blending is completed, extruding and granulating to obtain a composite material; the composite material prepared by the invention has the advantages of low cost and excellent impact resistance, ultraviolet resistance and aging resistance, and has good applicability for preparation of outdoor beautification housing products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a beautifying cover shell of a composite material and a preparation method thereof. Background Art

[0002] In modern society, as the use environment of existing beautification covers becomes increasingly complex and diverse, especially when exposed outdoors for a long time, the beautification covers in related technologies have poor impact resistance. When encountering strong winds, impacts from foreign objects, etc., they are prone to damage, affecting their protective function for internal equipment such as air conditioners. At the same time, beautification covers often work outdoors and it is difficult to effectively block the erosion of ultraviolet rays, causing the surface of the cover to age and fade easily, which not only affects the appearance but may also reduce its mechanical properties. Long-term exposure to wind, sun, temperature changes and other factors make the cover prone to brittleness and cracking, shortening its service life and increasing the frequency and cost of maintenance and replacement.

[0003] Chinese patent CN102863763A discloses a method for preparing a polycarbonate alloy material toughened by polypropylene. The polycarbonate alloy material toughened by polypropylene is prepared by mixing polycarbonate resin, polypropylene, maleic anhydride grafted polypropylene resin, maleic anhydride grafted POE resin, anti-aging agent and lubricant in a mass ratio of (220-250):(35-43):(5-11):(10-16):(0.4-0.8):(1.8-2.5). The impact strength of the polycarbonate alloy material toughened by polypropylene prepared by the invention is 31-38KJ / m 2 , which needs to be further improved; Chinese patent CN113943458B discloses a polycarbonate / polypropylene alloy material and a preparation method thereof, wherein the polycarbonate / polypropylene alloy material comprises polycarbonate, polypropylene, quaternary ammonium salt-modified graphene oxide volume-enhancing rice particles and processing aids in a mass ratio of (15-85):(10-70):(1-20):(0-3). The alloy material obtained by the invention has good aging resistance, can also play a good volume-enhancing role without reducing strength, but needs to further increase the anti-ultraviolet performance to expand the scope of use. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a beautification cover made of composite materials and a preparation method thereof, which solves the technical problem in the related art that the impact resistance, UV resistance and aging resistance of the beautification cover need to be further improved.

[0005] In order to achieve the above object, the present invention provides a method for preparing a beautified cover of a composite material, comprising the following steps:

[0006] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane uniformly, heating for reaction, centrifuging and drying after the reaction is completed to obtain amino titanium dioxide;

[0007] Step (2) mixing aminated titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene, heating, reacting, and after the reaction is completed, distilling under reduced pressure to obtain aminated titanium dioxide grafted polypropylene carbonate;

[0008] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide, heating for reaction, and performing reduced pressure distillation after the reaction is completed to obtain modified polypropylene carbonate;

[0009] Step (4) in an inert gas atmosphere, the modified polypropylene carbonate, polypropylene and an initiator are mixed, heated for reaction, and the reaction is completed to obtain an intermediate I;

[0010] The intermediate I, glass fiber, silicone rubber, antioxidant, UV absorber and lubricant are melt-blended, and after the melt-blending is completed, the mixture is extruded and granulated to obtain a composite material;

[0011] The composite material is added into the injection molding machine, melted at high temperature, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material.

[0012] Preferably, the preparation method of isocyanate-terminated polypropylene carbonate is as follows:

[0013] The polypropylene carbonate and hexamethylene diisocyanate are melt-blended to obtain isocyanate-terminated polypropylene carbonate;

[0014] The temperature of melt blending is 130-145°C, and the time of melt blending is 10-15 minutes.

[0015] Preferably, the mass ratio of nano-titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane is (80-100):(1800-3800):(50-70); the reaction temperature is 55-65° C., and the reaction time is 7-9 hours.

[0016] Preferably, the mass ratio of amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene is (60-80):(2000-2800):(2-4):(5000-7000); the reaction temperature is 80-100° C., and the reaction time is 2-4 hours.

[0017] Preferably, the mass ratio of amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide is (60-100):(280-320):(1-3):(600-1000); the reaction temperature is 80-90°C, and the reaction time is 26-38h.

[0018] Preferably, the mass ratio of modified polypropylene carbonate, polypropylene, initiator, glass fiber, silicone rubber, antioxidant, UV absorber and lubricant is (30-50):(18-26):(1-2):(4-6):(8-10):(2-4):(2-4):(1.2-1.6).

[0019] Preferably, the initiator is benzoyl peroxide.

[0020] Preferably, in step (4), the first heating reaction condition is: reacting at a temperature of 85-95° C. for 3-5 hours.

[0021] Preferably, the antioxidant is any one of antioxidant 1010 and antioxidant 168 .

[0022] Preferably, the UV absorber is ultraviolet absorber UV-326.

[0023] Preferably, the lubricant is polyethylene wax.

[0024] Preferably, the composite material beautifying cover is prepared by the method for preparing the composite material beautifying cover.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. In the present invention, nano titanium dioxide is a heat-resistant inorganic material of nanostructure. Appropriate addition can improve the thermal stability and mechanical properties of the matrix. Titanium dioxide can absorb and scatter ultraviolet rays under ultraviolet light to achieve the effect of ultraviolet resistance. At the same time, due to its small size, titanium dioxide can be modified to effectively avoid the agglomeration of titanium dioxide, and can be evenly dispersed to maintain its functional stability. 3-aminopropyltriethoxysilane is used as an organic silane, in which the silicon-oxygen bond energy is large, which can effectively improve thermal stability and increase aging resistance, and the long-chain structure can provide certain flexibility. The amino group in the aminated titanium dioxide reacts with the isocyanate group in the isocyanate-terminated polypropylene carbonate to obtain a more stable urea group. The presence of the urea group can improve the mechanical stability of the material, so that the material has good strength, toughness, etc. The urea group helps to maintain the elasticity and wear resistance of the material, so that it is not easy to be damaged under long-term use and stress.

[0027] 2. In the present invention, the added 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propylene)phenol has certain UV resistance and aging resistance. The hydroxyl group in 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propylene)phenol can react with the isocyanate group in the amino titanium dioxide grafted polypropylene carbonate to generate a carbamate group, thereby obtaining a modified polypropylene carbonate. The carbamate group contained in the modified polypropylene carbonate can further increase the thermal stability, and the carbamate group can enable the material to maintain good physical and chemical properties under long-term exposure to rainwater and other environments, thereby extending the service life of the material. At the same time, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propylene)phenol can cooperate with nano titanium dioxide and UV absorber to further increase the UV resistance of the material. The benzotriazole group in 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol has a strong electron-withdrawing property. The presence of this group enables the molecule to interact with external energy (such as shock waves), especially to absorb external mechanical energy through molecular vibration and bending. The combination of rigidity and flexibility of this structure can help the molecule effectively absorb energy when subjected to external impact; the methyl group (-CH3) it contains can increase the flexibility of the molecule, help it deform under external impact, and help improve the impact resistance of the material.

[0028] 3. In the present invention, polypropylene carbonate has good transparency, degradability, low price and good impact resistance; polypropylene has good comprehensive performance, rich raw material sources and simple production process. Modified polypropylene carbonate can react with polypropylene under the action of initiator benzoyl peroxide to obtain intermediate I because it contains unsaturated carbon-carbon double bonds; the two are stably connected by chemical bonds, and the compatibility is better, which helps to improve the stability of the material in ultraviolet and thermal oxygen environments, and at the same time improves the impact resistance. Glass fiber is used to strengthen the strength and impact resistance of the material; silicone rubber has high flexibility, which enables it to maintain good elasticity and flexibility in a large temperature range, and in low temperature environments, the molecular structure of silicone rubber enables it to still maintain good elasticity and flexibility, showing excellent cold resistance. This allows the composite material containing silicone rubber to still work normally under low temperature conditions, and is not prone to embrittlement, cracking and other problems.

[0029] 4. The present invention provides a composite material with excellent impact resistance, UV resistance and aging resistance through innovative materials and preparation methods. The beautified cover prepared by the material not only prolongs the service life, but also reduces the maintenance cost; and can ensure stable operation in a certain degree of harsh environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1The figure is a process flow chart of preparing the beautified cover of the composite material in the present invention;

[0031] Figure 2 This is a schematic diagram of the reaction for preparing amino titanium dioxide grafted polypropylene carbonate in the present invention;

[0032] Figure 3 This is a schematic diagram of the reaction for preparing modified polypropylene carbonate in the present invention;

[0033] Figure 4 It is a bar chart showing the impact resistance test results of the composite materials prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment provides a method for preparing a composite material beautification cover, comprising the following steps:

[0037] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 80:1800:50, reacting at 55° C. for 9 hours, centrifuging after the reaction is completed, and drying at 80° C. for 8 hours to obtain amino titanium dioxide;

[0038] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 60:2000:2:5000, heating, reacting at 80° C. for 4 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 60° C. for 4 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0039] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 60:280:1:600, heating, reacting at 80°C for 38h, and after the reaction is completed, performing reduced pressure distillation at 0.08MPa and 50°C for 5h to obtain modified polypropylene carbonate;

[0040] Step (4) mixing modified polypropylene carbonate, polypropylene and benzoyl peroxide, heating, and reacting at 85° C. for 5 h, and completing the reaction to obtain intermediate I;

[0041] The intermediate I, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax were melt-blended at 170° C. for 15 min, extruded and granulated to obtain a composite material;

[0042] The composite material is added into the injection molding machine, melted at a high temperature of 180°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0043] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, benzoyl peroxide, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 30:18:1:4:8:2:2:1.2.

[0044] Example 2

[0045] This embodiment provides a method for preparing a composite material beautification cover, comprising the following steps:

[0046] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 85:2300:55, reacting at 57° C. for 8.5 hours, centrifuging after the reaction is completed, and drying at 85° C. for 7.5 hours to obtain amino titanium dioxide;

[0047] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 65:2200:2.5:5500, heating, reacting at 85°C for 3.5 hours, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 62°C for 3.5 hours to obtain amino titanium dioxide grafted polypropylene carbonate;

[0048] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 70:290:1.5:700, heating, reacting at 82°C for 35h, and after the reaction is completed, performing reduced pressure distillation at 0.08MPa and 52°C for 4.5h to obtain modified polypropylene carbonate;

[0049] Step (4) mixing modified polypropylene carbonate, polypropylene and benzoyl peroxide, heating, and reacting at 87° C. for 4.5 h, and completing the reaction to obtain intermediate I;

[0050] The intermediate I, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax were melt-blended at 175° C. for 14 minutes, extruded and granulated to obtain a composite material;

[0051] The composite material is added into the injection molding machine, melted at a high temperature of 185°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0052] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, benzoyl peroxide, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 35:20:1.3:4.5:8.5:2.5:2.5:1.3.

[0053] Example 3

[0054] This embodiment provides a method for preparing a composite material beautification cover, comprising the following steps:

[0055] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 90:2800:60, reacting at 60° C. for 8 h, centrifuging after the reaction is completed, and drying at 90° C. for 7 h to obtain amino titanium dioxide;

[0056] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 70:2400:3:6000, heating, reacting at 90° C. for 3 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 65° C. for 3 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0057] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 80:300:2:800, heating, reacting at 85°C for 32h, and after the reaction is completed, performing reduced pressure distillation at 0.08MPa and 55°C for 4h to obtain modified polypropylene carbonate;

[0058] Step (4) mixing modified polypropylene carbonate, polypropylene and benzoyl peroxide, heating, and reacting at 90° C. for 4 h, and completing the reaction to obtain intermediate I;

[0059] The intermediate I, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax were melt-blended at 180° C. for 13 min, extruded and granulated to obtain a composite material;

[0060] The composite material is added into the injection molding machine, melted at a high temperature of 190°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0061] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, benzoyl peroxide, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 40:22:1.5:5:9:3:3:1.4.

[0062] Example 4

[0063] This embodiment provides a method for preparing a composite material beautification cover, comprising the following steps:

[0064] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 95:3300:65, reacting at 62° C. for 7.5 hours, centrifuging after the reaction is completed, and drying at 95° C. for 6.5 hours to obtain amino titanium dioxide;

[0065] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 75:2600:3.5:6500, heating, reacting at 95° C. for 2.5 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 67° C. for 2.5 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0066] Step (3) Aminated titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 90:310:2.5:900 are mixed, heated, reacted at 87°C for 29h, and after the reaction is completed, vacuum distilled at 0.08MPa and 57°C for 3.5h to obtain modified polypropylene carbonate;

[0067] Step (4) mixing modified polypropylene carbonate, polypropylene and benzoyl peroxide, heating, and reacting at 92° C. for 3.5 hours, and completing the reaction to obtain intermediate I;

[0068] The intermediate I, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax were melt-blended at 185° C. for 12 minutes, extruded and granulated to obtain a composite material;

[0069] The composite material is added into the injection molding machine, melted at a high temperature of 195°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0070] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, benzoyl peroxide, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 45:24:1.8:5.5:9.5:3.5:3.5:1.5.

[0071] Example 5

[0072] This embodiment provides a method for preparing a composite material beautification cover, comprising the following steps:

[0073] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 100:3800:70, reacting at 65° C. for 7 h, centrifuging after the reaction is completed, and drying at 100° C. for 6 h to obtain amino titanium dioxide;

[0074] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 80:2800:4:7000, heating, reacting at 100° C. for 2 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 70° C. for 2 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0075] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 100:320:3:1000, heating, reacting at 90°C for 26h, and after the reaction is completed, performing reduced pressure distillation at 0.08MPa and 60°C for 3h to obtain modified polypropylene carbonate;

[0076] Step (4) mixing modified polypropylene carbonate, polypropylene and benzoyl peroxide, heating, and reacting at 95° C. for 3 h, and completing the reaction to obtain intermediate I;

[0077] The intermediate I, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax are melt-blended at 190° C. for 10 min, extruded, and granulated to obtain a composite material;

[0078] The composite material is added into the injection molding machine, melted at a high temperature of 200°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0079] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, benzoyl peroxide, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 50:26:2:6:10:4:4:1.6.

[0080] Example 6

[0081] This embodiment provides a method for preparing isocyanate-terminated polypropylene carbonate, comprising the following steps:

[0082] Polypropylene carbonate (PPC) and hexamethylene diisocyanate in a mass ratio of 800:15 were melt-blended at 130° C. for 10 min. After the blending was completed, the mixture was dried at 70° C. for 14 h to obtain isocyanate-terminated polypropylene carbonate.

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing a composite material beautification cover, comprising the following steps:

[0085] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 80:1800:50, reacting at 55° C. for 9 hours, centrifuging after the reaction is completed, and drying at 80° C. for 8 hours to obtain amino titanium dioxide;

[0086] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 60:2000:2:5000, heating, reacting at 80° C. for 4 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 60° C. for 4 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0087] Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide in a mass ratio of 60:280:1:600, heating, reacting at 80°C for 38h, and after the reaction is completed, performing reduced pressure distillation at 0.08MPa and 50°C for 5h to obtain modified polypropylene carbonate;

[0088] Step (4) melt-blending the modified polypropylene carbonate, polypropylene, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax at 170° C. for 15 min, extruding and granulating to obtain a composite material;

[0089] The composite material is added into the injection molding machine, melted at a high temperature of 180°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0090] Among them, the mass ratio of modified polypropylene carbonate, polypropylene, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 31:18:4:8:2:2:1.2.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a composite material beautification cover, comprising the following steps:

[0093] Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane in a mass ratio of 80:1800:50, reacting at 55° C. for 9 hours, centrifuging after the reaction is completed, and drying at 80° C. for 8 hours to obtain amino titanium dioxide;

[0094] Step (2) mixing amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene in a mass ratio of 60:2000:2:5000, heating, reacting at 80° C. for 4 h, and after the reaction is completed, performing reduced pressure distillation at 0.08 MPa and 60° C. for 4 h to obtain amino titanium dioxide grafted polypropylene carbonate;

[0095] Step (3) melt-blending amino titanium dioxide grafted polypropylene carbonate, polypropylene, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax at a temperature of 170° C. for 15 minutes, extruding and granulating to obtain a composite material;

[0096] The composite material is added into the injection molding machine, melted at a high temperature of 180°C, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material;

[0097] Among them, the mass ratio of amino titanium dioxide grafted polypropylene carbonate, polypropylene, glass fiber, silicone rubber, antioxidant 1010, ultraviolet absorber UV-326 and polyethylene wax is 31:18:4:8:2:2:1.2.

[0098] The isocyanate-terminated polypropylene carbonate in Examples 1-5 and Comparative Examples 1-2 are all prepared from the isocyanate-terminated polypropylene carbonate prepared in Example 6.

[0099] In the embodiments and comparative examples of the present invention, polypropylene carbonate is from Jiangsu Zhongke Jinlong Chemical Co., Ltd., with a number average molecular weight of 80,000; polypropylene is purchased from PetroChina Daqing Petrochemical Company, with model T30S and a melt flow index (MFI) of 3.0 g / min; silicone rubber is from Jinan Xinhanbang Chemical Technology Co., Ltd.; nano titanium dioxide is from Xuancheng Jingrui New Materials Co., Ltd., with model JR05 and an average particle size of 5 nm; toluene is from Tianjin Fuyu Fine Chemical Co., Ltd., with CAS number: 108-88-3; glass fiber is glass fiber powder provided by Shijiazhuang Lishang Mineral Products Processing Co., Ltd., with item number: 80; 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol is from Shanghai McLean Biochemical Technology Co., Ltd., with CAS number: 2170-39-0.

[0100] The composite materials in Examples 1-5 and Comparative Examples 1-2 were tested accordingly, and the test results are as follows:

[0101] (1) Impact resistance test: The composite materials in Examples 1-5 and Comparative Examples 1-2 were made into strips with a size of 80 mm×10 mm×4 mm, and the impact resistance was tested. The impact strength test was carried out on a XCJD pendulum impact tester. The notch depth was 20% of the strip thickness. Each sample was tested 5 times and the average value was taken. The specific test results are shown in Table 1:

[0102] Table 1

[0103]

[0104] As shown in Table 1, the composite material prepared by the present invention has good impact resistance. Embodiment 1 is compared with Comparative Example 1, and the modified polypropylene carbonate containing unsaturated carbon-carbon double bonds and polypropylene react under the action of initiator benzoyl peroxide to obtain intermediate I, and such reaction makes the material form a more effective cross-linked structure inside, and compatibility is improved, thereby improving the impact resistance of the material; and benzoyl peroxide is not used in Comparative Example 1, which may cause the material internal structure to be relatively loose, and the impact resistance is poor. In Comparative Example 1, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propylene) phenol can absorb and dissipate energy in the composite material, and when the material is impacted, the impact energy can cause the material to deform, and it can convert part of the impact energy into heat or other forms of energy by its own molecular motion (such as vibration, rotation, etc.), thereby reducing the possibility of energy accumulation in the material causing crack generation and expansion, and enhancing the ability of the material to resist impact damage, once lacking, its impact resistance naturally reduces, so the impact resistance of Comparative Example 1 is better than Comparative Example 2.

[0105] (2) Aging performance test: The composite materials in Examples 1-5 and Comparative Examples 1-2 were made into strips with a size of 80 mm×10 mm×4 mm, and subjected to UV aging and thermal oxygen aging tests, respectively. The samples were placed in a UV aging test chamber and a thermal aging test chamber for 10 days of aging treatment, respectively. A xenon lamp with a power of 35 W was used during the UV aging process, and the temperature of the thermal aging test was 50° C. After the treatment was completed, the samples were taken out and subjected to the same impact resistance test as in Table 1. Each sample was tested 5 times, and the retention rate (%) of the notched impact strength was recorded. The specific test results are shown in Table 2:

[0106] Table 2

[0107]

[0108] According to the test results in Table 2, the composite material prepared in the present invention still has excellent mechanical properties after UV aging and thermal oxidative aging. After UV aging, the average retention rate of the notched impact strength of the composite material is 93.08%; after thermal oxidative aging, the retention rate of the notched impact strength of the composite material is the best in Example 1, with a value of 90.37%. In the process of preparing the modified polypropylene carbonate in Example 1, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol is added. The substance may have good ultraviolet absorption and anti-aging functions, and can effectively protect the material from damage by ultraviolet light and thermal oxygen, thereby improving the ultraviolet resistance and aging resistance. The isocyanate group in the isocyanate-terminated polypropylene carbonate reacts with the amino group in the amino titanium dioxide to form a stable urea bond structure, which is beneficial to stability, ultraviolet resistance and aging resistance. The modified polypropylene carbonate contains unsaturated carbon-carbon double bonds and can react with polypropylene under the action of the initiator benzoyl peroxide to obtain an intermediate I with better compatibility. The compatibility and dispersibility in Comparative Example 1 are lower than those in Example 1, so the UV resistance and aging resistance of Comparative Example 1 are lower than those in Example 1; Comparative Example 2 lacks 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol compared to Comparative Example 1, so the UV resistance and aging resistance of Comparative Example 1 are better than those of Comparative Example 2.

[0109] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a composite material beautification cover, characterized in that: The following steps are involved: Step (1) mixing nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane uniformly, heating for reaction, centrifuging and drying after the reaction is completed to obtain amino titanium dioxide; Step (2) mixing aminated titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene, heating, reacting, and after the reaction is completed, distilling under reduced pressure to obtain aminated titanium dioxide grafted polypropylene carbonate; Step (3) mixing amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide, heating for reaction, and performing reduced pressure distillation after the reaction is completed to obtain modified polypropylene carbonate; Step (4) in an inert gas atmosphere, the modified polypropylene carbonate, polypropylene and an initiator are mixed, heated for reaction, and the reaction is completed to obtain an intermediate I; The intermediate I, glass fiber, silicone rubber, antioxidant, UV absorber and lubricant are melt-blended, and after the melt-blending is completed, the mixture is extruded and granulated to obtain a composite material; The composite material is added into the injection molding machine, melted at high temperature, and the molten material is injected into the mold by the injection molding machine, and quickly cooled to obtain a beautified cover of the composite material.

2. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The preparation method of isocyanate-terminated polypropylene carbonate is as follows: The polypropylene carbonate and hexamethylene diisocyanate are melt-blended to obtain isocyanate-terminated polypropylene carbonate.

3. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The mass ratio of nano titanium dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane is (80-100):(1800-3800):(50-70); the reaction temperature is 55-65° C., and the reaction time is 7-9 hours.

4. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The mass ratio of amino titanium dioxide, isocyanate-terminated polypropylene carbonate, dibutyltin dilaurate and toluene is (60-80):(2000-2800):(2-4):(5000-7000); the reaction temperature is 80-100° C., and the reaction time is 2-4 hours.

5. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The mass ratio of amino titanium dioxide grafted polypropylene carbonate, 2-(2H-benzotriazole-2-yl)-4-methyl-6-(2-propenyl)phenol, dibutyltin dilaurate and N,N-dimethylformamide is (60-100):(280-320):(1-3):(600-1000); the reaction temperature is 80-90°C and the reaction time is 26-38h.

6. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The mass ratio of modified polypropylene carbonate, polypropylene, initiator, glass fiber, silicone rubber, antioxidant, UV absorber and lubricant is (30-50):(18-26):(1-2):(4-6):(8-10):(2-4):(2-4):(1.2-1.6).

7. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The initiator is benzoyl peroxide.

8. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: In step (4), the first heating reaction condition is: reacting at 85-95°C for 3-5h.

9. The method for preparing a composite material beautifying cover according to claim 1, characterized in that: The antioxidant is any one of antioxidant 1010 and antioxidant 168.

10. A composite material beautifying cover shell prepared by the method for preparing a composite material beautifying cover shell according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Automotive heat-aging-resistant glass fiber reinforced PP material and preparation method thereof

    CN117430839A

  • Production of modified propylene polymer

    JP1994211914A